Essentials of Rorschach assessment comprehensive system and R-PAS - Gurley, Jessica R. (Essentials of psychological assessment., 2017)
"The clinician's practical guide to both methods of Rorschach personality assessment Essentials of Rorschach Assessment provides an invaluable resource for clinicians, offering the only step-by-step guidance toward all aspects of the Rorschach Comprehensive System and Rorschach Performance Assessment System (R-PAS). Beginning with an overview of the tests' history and development, the discussion delves into each test separately before placing the two side by side for direct comparison of administration, coding, and interpretation. The same case study is used for both tests, providing a start-to-finish example of how the Comprehensive System and R-PAS differ, and practical resources including checklists, charts, and sample forms help ease implementation, use, and transition. Thorough explanations break down the jargon and technical language to give clinicians a clearer understanding of both tests without sacrificing precision or depth of information, providing a quick and easy reference for Rorschach personality assessment. While the Rorschach Comprehensive System is the most established version of the inkblot test, the recent development of R-PAS provides an alternative that may be more advantageous in some situations. This book provides complete guidance toward both tests, with expert advice on transitioning between the two. Understand the theoretical underpinnings of the Rorschach systems Learn how to administer, score, and interpret the tests effectively Compare the Rorschach Comprehensive and R-PAS through side-by-side case studies Access useful resources for coding, scoring, administration, interpretation, and more The Rorschach Inkblot Test assesses unconscious perceptions, thought processes, needs, motivations, and conflicts without relying on self-reporting, and can be useful in assessing an individual for severe mental illness. Essentials of Rorschach Assessment brings clinicians up to speed quickly and easily to help them get the most out of the system"--Provided by publisher.